Optimizing Electroplating Process Parameter And Sn-Plating Thickness Uniformity Using Modified Shielding - Suieb, Nurhanim (2020)
Uneven plating thickness distribution across plated surface has become a major challenge in electroplating industry even for advanced plating technology today due to complexity of package design. LPL HD package encounter low plating thickness on the heatsink area, but thicker on lead area. Due to this phenomena, manufacturer encounter high losses due to plating thickness not meeting required package design specification. A number of natural phenomena occur in the electroplating process has cause the material to be deposited unevenly on the leadframe. One of the factors is due to complexity of lead frame geometry design and size of targeted surface area. The shields offer a high resistance path to the material ions from anodes to cathode. Therefore this research will study the most appropriate process parameters (current and speed) of electroplating to improve Sn-plating thickness uniformity using modified mechanical shielding. Taguchi method is adopted to reduce the size of experiment and optimize the process parameters simultaneously. As a result, new parameter has been established which offer ideal plating thickness with less variation and stable Cpk. This is due to excellent design of shielding, the plating thickness on complex leadframes able to achieve good uniformity. The modified shielding proven has effectively reduce the thickness variation on lead as it reduces the high current setting subject to it. While the effect of optimized parameters successfully assessed thoroughly during validation phase with convincing result. The optimized parameter is current 120 A and speed 3.46 m/min with 90% agreement on lead while only 489% on heatsink after validate with production condition.